Usuários de informação: estudo realizado no curso de graduação em História, da Universidade Federal Fluminense - Rosa, Regina Célia Pereira da (1982)
A survey of students in the Graduate Course in Histrory, in the Universidade Federal Fluminense, was conducted to determine the extent to which the library was used as an information source. It was meant to establish: - if the students used such sources in a reasonable way; - if they were stimulated to do so, and if they would like to attend curses on how to use the above mentioned sources. Based on the results, procedures were suggested as to the objectives, methods, planning and accomplishing the education in the use of information in the University. The data were collected by means of questionnaires distributed to the students in December, 1978, during the registration period. These data were manually tabled, and percentual indices were calculated so as to determine similar behavior frequency.It was found that the use of the library services, except the loan service, was insignificant. According to the majority of the students, the textbook, as an information source, was the most used material. It was noticed that the students were interested in participating of courses on how to use libraries and their resources. To accomplish it, that is, to make it possible for the students to be able to take the best from the library resources, it was recommended that a better librarian/teacher/students relationship be implemented.